2013
DOI: 10.1111/ijfs.12209
|View full text |Cite
|
Sign up to set email alerts
|

The impact of strawflower and mistletoe extract on quality properties of rainbow trout fillets

Abstract: Many plants, including strawflower and mistletoe, contain antioxidants and antimicrobials, which can increase the shelf life of seafood. The main aim of this study was to investigate the effect of mistletoe and strawflower extracts at doses of 0.5% (w/v) on the sensory, chemical and microbiological properties of rainbow trout fillets during 27 days of storage at 2 AE 1°C. The phenolic compounds in these plants have been studied, but their effects on food quality and storage properties have not been reported. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…This effect was due to the phenolic compounds of sesame. The present study result is similar to [33], who found that sea bream and sea bass llets treated with nanoemulsion using sun ower oil lower the FFA value than the control group [34]. The result was also similar to the present study as he concluded that the initial level of fee fatty acid was low, but as storage time of llets was increased, the value of free fatty acid was also increased.…”
Section: Discussionsupporting
confidence: 90%
“…This effect was due to the phenolic compounds of sesame. The present study result is similar to [33], who found that sea bream and sea bass llets treated with nanoemulsion using sun ower oil lower the FFA value than the control group [34]. The result was also similar to the present study as he concluded that the initial level of fee fatty acid was low, but as storage time of llets was increased, the value of free fatty acid was also increased.…”
Section: Discussionsupporting
confidence: 90%
“…Phenolics compounds (e.g., flavonoids and chalcones, phthalides, a-pyron derivatives and terpenoids), essential oils, volatiles and fatty acids have been found in strawflowers. Strawflower suppressed biogenic amine accumulation in fish fillets [ 160 ]. The application of strawflower or mistletoe extract on trout fillets suppressed tyramine accumulation in fish meat ( p < 0.05), although the fish treated with mistletoe extract had the highest level of tyramine at 20 days [ 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…Strawflower suppressed biogenic amine accumulation in fish fillets [ 160 ]. The application of strawflower or mistletoe extract on trout fillets suppressed tyramine accumulation in fish meat ( p < 0.05), although the fish treated with mistletoe extract had the highest level of tyramine at 20 days [ 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rainbow trout (Oncorhynchus mykiss) is a fatty fish species with high commercial value and very appreciated by European consumers (Rezaei andHosseini 2008, Özogul et al 2013). Trout, as fatty fish variety, is very prone to deterioration (Pereira de Abreu et al 2012, Özogul et al 2013), precisely to its high oil/fat content (Fraser and Sumar 1998).…”
Section: Introductionmentioning
confidence: 99%